The Interplay of Profitability and Social Responsibility in Achieving Institutional Excellence: An Exploratory Study in Government and Private Hospitals in Jeddah, Kingdom of Saudi Arabia (Global Journal of Management and Business Research, 2024)
Abstract not found
Keywords: healthcare management; social responsibility; financial viability; patient satisfaction; institutional excellence